Harmonised culture procedures minimise but do not eliminate mesenchymal stromal cell donor and tissue variability in a decentralised multicentre manufacturing approach - Calcat-i-Cervera, Sandra; Rendra, Erika; Scaccia, Eleonora; Amadeo, Francesco; Hanson, Vivien; Wilm, Bettina; Murray, Patricia; O’Brien, Timothy; Taylor, Arthur; Bieback, Karen (Stem cell research & therapy, 2023)
Mesenchymal stromal cells (MSCs), commonly sourced from adipose tissue, bone marrow and umbilical cord, have been widely used in many medical conditions due to their therapeutic potential. Yet, the still limited understanding of the underlying mechanisms of action hampers clinical translation. Clinical potency can vary considerably depending on tissue source, donor attributes, but importantly, also culture conditions. Lack of standard procedures hinders inter-study comparability and delays the progression of the field. The aim of this study was A- to assess the impact on MSC characteristics when different laboratories, performed analysis on the same MSC material using harmonised culture conditions and B- to understand source-specific differences.